Strategies for better integrating nutrient supplementation and dietary diversity approaches for stunting reduction and improved nutrition outcomes: A Rwandan case study - Warner, James; Marivoet, Wim; Covic, Namukolo M.; Umugwaneza, M. (Wiley, 2023)
Increased attention to the health and nutritional status of people in low‐income countries has led to the development and budgeting for food and nutrition policies. While current policy discussions generally acknowledge the need for better integrating nutrition‐sensitive approaches into current nutrition‐specific health interventions, most do not weigh the costs and merits or potential synergies.The overall objective of this article is to gain insight into the types of interventions that policy‐makers can select and combine to sustainably improve nutrition outcomes in Rwanda.Making use of the Lives Saved Tool (LiST) combined with linear programming (LP) techniques applied to food consumption data, this article applies a cost–benefit analysis to Rwanda on two distinct intervention bundles targeted at children and pregnant women. The first entails a set of six nutrient supplementation interventions; the second involves dietary diversification.Whereas both intervention types yield comparable results with respect to short‐term cost effectiveness, the diet diversity approach clearly outperforms nutrient supplementation interventions when aspects of behavioural change, fiscal dependency, and broader economic spillovers are considered in the longer term. Given that undernutrition calls for immediate action while food systems cannot be transformed overnight, abruptly implementing the diet diversity approach is neither effective nor politically feasible.Based on the article's findings, future policies in Rwanda should consider adopting a more comprehensive strategy that integrates a set of near‐term implementable health/nutrition interventions, for immediate impacts on stunting cases, with medium‐term investments to help establish a food system capable of increasing dietary diversity and sustainably improving nutritional outcomes of the population.